Perceraian Era Pandemi Covid-19 - Fakhry 'Afifurahman; Madhory Madhory; Tasya Ramadhini; Isra Islamiyah; Ridho Bayu Samudra (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
During the COVID-19 pandemic, divorce cases in the city of Tangerang experienced an increase. In particular, this paper aims to identify how high divorce cases occurred during the pandemic, but also to analyze the factors/conditions that led to an increase in divorce cases based on the results of religious court decisions regarding divorce. This study uses a qualitative approach with a descriptive analytical approach that utilizes data sourced from scientific articles in Google Scholar, Garuda, Sinta and journals managed by various institutions. The understanding of divorce in marriage according to the Islamic point of view is the last door when there is no way out to solve problems that occur in the household. And in article 39 of the marriage law it is explained that divorce can only be carried out in front of a court session and not with a court decision. The divorce rate in Tangerang City throughout 2021 is 3,545 cases. This figure has increased by about 14 percent compared to 2020 with 3,041 cases. In 2020 the highest cause of divorce is economic with 6,001 cases, and in 2021 the highest cause of divorce is disputes and quarrels with 2,026 cases. This increase in divorce certainly results in several impacts, such as psychological weakness in children, traumatic events, changes in roles and status, to difficulty adjusting. The government needs to pay special attention to increasing divorce cases by optimizing mediation by religious courts.